2002
DOI: 10.1034/j.1600-079x.2002.01107.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin protects against gastric ulceration and increases the efficacy of ranitidine and omeprazole in reducing gastric damage

Abstract: The antiulcer effect of melatonin on gastric lesions caused by restraint-cold stress was studied with the intent of determining the mechanism of action of this agent. Melatonin dose-dependently prevented restraint-cold stress-induced gastric damage with around 90% inhibition at a dose of 60 mg/kg BW. When compared with already marketed antiulcer drugs such as ranitidine and omeprazole, melatonin was found to be more effective than ranitidine but less effective than omeprazole in preventing stress ulcer. As str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 56 publications
6
41
0
Order By: Relevance
“…Functional connections between vitamin D and melatonin have been pointed out (72,73) and are considered relevant for harmonious regulations in a natural environment. Evidence exists in the literature for melatonin actions on the digestive system as well, such as protective effects against gastric ulceration (74,75) and periodontal inflammatory disease (76), uptake of melatonin-related compound in submandibular gland (77) and secretion of nerve growth factor (78). Identification of melatonin targets is still lacking but would be indispensable for clarification and assessment of functional relationships between these hormonal regulators and solar zeitgebers (72).…”
Section: Discussionmentioning
confidence: 99%
“…Functional connections between vitamin D and melatonin have been pointed out (72,73) and are considered relevant for harmonious regulations in a natural environment. Evidence exists in the literature for melatonin actions on the digestive system as well, such as protective effects against gastric ulceration (74,75) and periodontal inflammatory disease (76), uptake of melatonin-related compound in submandibular gland (77) and secretion of nerve growth factor (78). Identification of melatonin targets is still lacking but would be indispensable for clarification and assessment of functional relationships between these hormonal regulators and solar zeitgebers (72).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have compared melatonin' s e cacy in protecting against stress-induced gastric ulceration with widely used anti-ulcer medication such as ranitidine and omeprazole (Bandyopadhyay et al 2000(Bandyopadhyay et al , 2001(Bandyopadhyay et al , 2002. Ranitidine blocks histamine-stimulated acid secretion in the stomach while omeprazole, a substituted benzimidazole, completely interrupts acid secretion.…”
Section: Ranitidine and Omeprazolementioning
confidence: 99%
“…In the stomach, melatonin was found to inhibit acid secretion [6,7], and it induces duodenal HCO 3 -secretion in response to gastric acid [8]. Studies in animals showed that melatonin stimulates pancreatic enzyme secretion and improves the outcome of experimental pancreatitis [9][10][11].…”
Section: Introductionmentioning
confidence: 99%